Cardiomyopathy Associated With Coronary Arteriosclerosis in Free-Ranging Eurasian Lynx (Lynx lynx carpathicus). - Ryser-Degiorgis, Marie-Pierre; Robert, Nadia; Meier, Roman Kaspar; Zürcher-Giovannini, Samoa; Pewsner, Mirjam; Ryser, Andreas; Breitenmoser, Urs; Kovacevic, Alan; Origgi, Francesco C. (Frontiers in Veterinary Science, 2020)
The Eurasian lynx (subspecies Lynx lynx carpathicus) was reintroduced to Switzerland in the 1970's. Health monitoring of the reintroduced population started in the late 1980's. Since then, six lynx have been found affected by a myocardial disease. The earliest case was an animal that died after a field anesthesia. Two lynx were found dead, two were euthanized/culled because of disease signs, and one was hit by car. Two had a heart murmur at clinical examination. At necropsy, the first animal showed only lung edema but the other five had cardiomegaly associated with myocardial fibrosis. Three had multisystemic effusions. Histological examination of all six lynx showed mild to severe, multifocal, myocardial interstitial and perivascular fibrosis along with multifocal myocyte degeneration and loss, and replacement fibrosis. Moderate to severe multifocal arteriosclerosis with associated luminal stenosis of the small and medium-sized intramural coronary arteries and the presence of Anitschkow cells was also observed. The heart lesions may have led to sudden death in the first case and to a chronic right-sided heart failure in the remaining. None of the lynx showed lesions or signs suggestive of an acute or subacute infection. Given the common geographic origin of these animals and the severe loss of heterozygocity in this population, a genetic origin of the disease is hypothesized.